THE MULTICHANNEL AND OMNI-CHANNEL APPROACH CONCERNING BORN ONLINE SHOPS. The Influence of the Customer Experience. - Perotti, Veronica (My University, 2017)
Despite in the literature there is no a unique definition of Multichannel and Omni-channel, these approaches and strategies have been taken into account with an essential role within the modern marketing. Nevertheless, all definitions interpret them according to the different use and degree of integration of many different channels for the communication and the distribution. The presented work investigates on the reasons why born-online stores approach the multichannel, or omni-channel, strategy by opening bricks-and- mortars shops. On the basis of the above mentioned choice it is considered the influence of the customer experience. The referred concept is taken into account to understand if companies are customer oriented and if they want to improve the satisfaction of the clients, with the decision of opening physical stores. In addition, the experience is considered from customer’s point of view to understand if, and how, it could be an important element in the selection of the purchasing channel. The study is based on the analysis of both customers and firm. Therefore, consumers are analysed according to qualitative and quantitative methods: 25 customers’ semi- structured interviews and 255 customers’ online-base questionnaire are presented in the research. The firm, Glassing, allowed the researcher to have a semi-structured interview with one of the two owners. In both cases, costumers’ and firm’s ones, are asked about the online and offline shopping, customers’ experience and satisfaction, the channel selection and the channel integration. Final results and findings show that the bricks-and- mortars stores are still playing a fundamental role for both customers and the company. Albeit their relevance, it has emerged that the possibility to touch and try the products resulted to have a great relevance on customers’ purchasing channel decision.
Keywords: Experience; Marketing; Online Shopping; Multichannel; Omni-channel; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|